Evaluation of the use of farmyard manure on a guinea grass (Panicum maximum) - Stylo (Stylosanthes guianensis) mixed pasture - S. A., Ahmed; Abdul Halim, Ridzwan; Ramlan, Mohd Fauzi (Universiti Putra Malaysia Press, 2012)
The effects of different levels of farmyard manure (FYM) and inorganic phosphorus (P) and potassium(K) fertilizer application on the physiology, forage yield and quality of Stylo (Stylosanthes guianensis cv.Pauciflora) - guinea grass (Panicum maximum cv. Green panic) pasture grown on an acid soil in Malaysiawere evaluated in this study. The treatments were six rates of FYM application (0, 10, 20, 30, 40, 50 t FYM/ha and a combined application of 50 kg P with 50 kg K/ha) as triple-superphosphate and muriate of potash,respectively. Four consecutive cuttings were taken at 6-week intervals. Dry matter (DM) yield of guineaincreased linearly with increasing levels of FYM with rates of increase from 239 to 457 kg/ha per tonne increaseof the FYM applied. On the other hand, the DM yield of Stylo was found to decline with the increasing ratesof FYM. Crude protein (CP) concentration of guinea increased linearly from 9.27% to 11.93% from 0 to 50t FYM applications, while the CP concentration of Stylo increased from 17% to 20%. The photosyntheticrate, leaf area index and stomatal conductance of guinea significantly increased with the increasing rates ofthe FYM applied. On the contrary, acid detergent fibre and neutral detergent fibre concentrations of guineadeclined with the increasing rates of the FYM used. Meanwhile, the use of inorganic P and K fertilizers gavea higher yield and higher quality of both the species compared to the control at the first cut but they were notsignificantly different from the control at the fourth cut.